Analisis Willingness To Pay (WTP) Terhadap Skenario Aspek Teknis Dan Alam Hutan Kota Dalam Pengelolaan Berkelanjutan (Studi Di Hutan Kota Palu)” - aminudin, Rifkal; Umar, Syukur; Muis, Hasriani (Mitra Sains, 2022)
This research aims to identify visitors' perceptions of the environmental conditions of urban forests and calculate the WTP value for efforts to maintain forest environmental conditions. Using the CVM method is a survey technique to ask respondents about the value/price they give to commodities that do not have a market price, such as environmental goods. The results obtained, Respondents' Perceptions were assessed from several aspects, namely: Cleanliness, Beauty, Comfort, Coolness and Satisfaction. With respondents' average rating being "Quite good and good" and the aspect with the highest score being Beauty and Comfort with a score of 4.17, the average WTP for urban forests is IDR. 2,818.2, with the number of respondents willing to pay 253 out of the total respondents 269 and the total WTP or income that can be generated is IDR. 273,803,792 per year. Based on the total WTP value obtained, it can be used as a reference in developing and improving environmental services that can be offered and become an attraction for the city of Palu, so that more and more people visit the Palu city forest and can enjoy it continuously.